The controversial application of the sanctioning regime on the so-called organizational or commercial scab - Rodrigo Sanbartolomé, Francisco Agustín (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
Although the work of the legislator and the application of sanctioning norms by the Public Administrations is constitutionally limited, in favor of the legal security of citizens (art. 9.3 CE), by the principles of legality and typicality (art. 25.1 CE), currently, it is possible to find different examples of cases in which the Administration sanctions (and the judges confirms) actions in order to subcontracting the tasks affected by the strike. Regardless of whether there is jurisprudence favorable to the recognition, for certain aspects or manifestations, of the so-called organizational or commercial scab, the truth is that these behaviors are not expressly contemplated in the literal wording of the sanctioning provision applicable to scab (art. 8.10 LISOS) generating, therefore, well-founded doubts about the legal admissibility of those sanctions. Based on this approach, this work begins with the conceptual analysis of the different types of scabs and the sanctioning precepts that are applicable to them and, after a careful study of the main principles that delimit the sanctioning activity of Public Administration, ends with a critical review of the most significant judicial decisions.